Educational Financing Management in the Era of Regional Autonomy - Lia Efriliyanti; Ade Akhmad Saputra; Edi Tedi; Puspa Rini; Afif Alfiyanto (Universitas Pahlawan Tuanku Tambusai, 2022)
This study aimed to determine the concept of education financing management in the era of regional autonomy. This research is a literature review or literature review to formulate education financing management in the era of regional autonomy. The results of this study indicate that budget leakage or in its most severe form, such as educational corruption, causes a reduction in the education budget, damages the mentality of the education bureaucracy, increases the burden of costs that must be borne by the community and decreases the quality of education services. The data shows that the education budget is an easy target for specific individuals to commit abuse. In addition, the education budget allocated to educational institutions must be supervised and monitored. Empirical conditions show that the actual receipt of education funds has yet to meet operational demands ideally. This is caused by various things that affect the provision of education funds, such as limited government funds, education tax policies have not been established, the ability of the community, especially parents, still varies in income compared to expenses that must be handled, as well as the private sector is still not much concerned about financial contributions to the implementation of education. Therefore, the implementation of education is the responsibility of all parties, in the sense that the implementation of education requires the support of various parties so that it can run as expected.